Layanan Bimbingan Kelompok dengan Pendekatan Kolaboratif untuk Meningkatkan Kemampuan Perencanaan Karier Siswa SMK - Kristiani Kristiani; Happy Karlina Marjo; Lara Fridani (Universitas Mathla'ul Anwar Banten, 2019)
GROUP GUIDANCE SERVICES WITH A COLLABORATIVE APPROACH TO IMPROVE CAREER PLANNING ABILITY IN VOCATIONAL STUDENTS. This study aims to improve career planning through Guidance Groups in AP-1 Class XI Students of 29 Jakarta Vocational School Odd Semester 2018/2019 Academic Year. After analyzing can be found more deeply, two factors can because, namely internal factors and external factors. Internal factors are the factors related to the guidance teacher as the implementer of counseling, including the skills and attitudes of the counselor. Guiding skills are the main factor in the success of counseling at school. External factors are factors that come from outside the supervise of the teacher, including the principal's policies, and students' knowledge and understanding of counseling. The problem examined in this study is how to improve the material guidance, service of career and to plan through group guidance methods can improve students' communication skills as a variable y while consulting service guidance as a variable x. Communication skills improvement was measured through questionnaires that contained interest in counseling, counseling, understanding of BK, trust in BK and attitudes towards counseling stating that students' interest in counseling would increase through group guidance methods arranged according to the sequence of student interests that could be verified.